Daya Terima, Kandungan Gizi dan Daya Antioksidan Formula Snack Bar Substitusi Tepung Ubi Jalar Ungu dan Tepung Biji Kelor Sebagai Jajanan Sehat Bagi Anak Sekolah - Rani Vindianti; Nurdiana Nurdiana; Hardianti Hardianti (PPNI UNIMMAN, 2024)
Snacks among school children still contain many unhealthy ingredients (high sugar salt and saturated fat) fulfillment of the nutritional needs of school children can be achieved by changing to healthier snacks, one of which is snack bars. Fulfillment of nutrients in making snack bars can be obtained from local food ingredients, namely purple sweet potato flour and moringa seed flour. The aim is to determine the acceptability, nutritional content and antioxidant power of snack bar formula substituted with purple sweet potato flour and moringa seed flour as a healthy snack for school children. The design used a completely randomized design (CRD) method. Formulation of making snack bar substitution of purple sweet potato flour and moringa seed flour with three treatments F1 (90%:10%), F2 (80%:20%), and F3 (70%:30%). Research Results: Based on the results of the acceptability test, the selected formulation is F2. The snack bar contains 33.769% protein, 8.941% fat, 30.22% carbohydrate, 29.546% moisture content, 1.81% ash content, and IC50 antioxidant power of 101.354 ppm (medium).